AJL macular buckle for the treatment of myopic foveoschisis with posterior staphyloma - Morawski, Krzysztof; Kozioł-Moszczyńska, Joanna; Kozicka, Katarzyna; Miniewicz, Joanna; Kubicka-Trząska, Agnieszka; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
The aim of the paper is to discuss a new treatment method of myopic foveoschisis with posterior staphyloma using pars plana vitrectomy with internal limiting membrane peeling and implantation of AJL macular buckle. The case of a 48-year-old woman admitted to our department due to myopic foveoschisis with posterior staphyloma of the left eye is presented. The patient underwent pars plana vitrectomy and implantation of AJL macular buckle. The anatomy of the posterior pole was improved as a result of retinal reattachment in the macular area confirmed clinically and with the deep range imaging optical coherence tomography. Postoperative visual acuity was also improved. We also achieved resolution of subjective symptoms such as metamorphopsia and relative scotoma in a visual field. AJL macular buckle implantation and vitrectomy with internal limiting membrane peeling can be an effective treatment of the myopic foveoschisis with posterior staphyloma.